Increased plasma brain-derived neurotrophic factor (BDNF) as a potential biomarker for and compensatory mechanism in mild cognitive impairment: A case-control study - Ng, Ted Kheng Siang (Impact Journals LLC, 2022)
10.18632/aging.203598